Emergency nurse practitioner practice analysis: Report and implications of the findings. Issue 10 (October 2018) - Tyler, Diane O.; Hoyt, Karen Sue; Evans, Dian Dowling; Schumann, Lorna; Ramirez, Elda; Wilbeck, Jennifer; Agan, Donna
ABSTRACT: Background and purpose: A practice analysis of nurse practitioners (NPs) working in emergency care was undertaken to define their job tasks and develop a specialty certification by examination. Method: In phase I, clinical experts created a qualitative description of domains of practice, tasks performed, knowledge required, and procedures performed by NPs in emergency care. Phase II involved validating the qualitative description through a national survey ( N = 474) of emergency nurse practitioners (ENPs). Evidence from the validation survey was used to create a test content outline for the ENP examination. Findings and Conclusions: The delineation of ENP practice validated by the survey (Cronbach alpha = 0.86–0.94 across rating scales) included 5 ENP practice domains: medical screening, medical decision-making/differential diagnoses, patient management, patient disposition and professional, legal and ethical practices. There were 22 job tasks across domains, 10 types of patient conditions/emergency types, 42 knowledge areas, and 68 procedures performed by ENPs. These resulted in a test blueprint providing the foundation for the ENP certification examination content validity. Implications for practice: Beyond certification, the practice analysis has the potential to further inform the scientific basis of emergency specialty practice. Additional uses include refining professional scope and standards of practice, job descriptions, performance appraisals, research, and policy development.